Criminal liability of seafarers and ship operators: A regulatory perspective on developments in environmental law - Ringbom Henrik (Routledge, 2022)
At first sight, civil and criminal liabilities have little in common. A number of key differences distinguish them, starting from their very objectives: one is aimed at compensating losses, while the other one at penalising unlawful behaviour. This chapter focuses on the interaction and inter-relationship between civil and criminal liability regimes in ship-source pollution. In the European Union (EU), the increased resort to criminal liability for environmental purposes has been particularly marked, in light of the relatively recent clarification of the EU’s competence in criminal matters. A very important concern with criminal penalties is that they, in practice, tend to be implemented through measures that affect the seafarers on-board the ship in question. As opposed to oil spills, air emissions do not happen as a result of isolated events or incidents of a one-off nature but are of a continuous operational nature. Compliance with the fuel quality rules entails significant costs for ship operators.
Ship Operations - New Risks, Liabilities and Technologies in the Maritime Sector